PENGEMBANGAN BUKU TEKS MEMBACA PEMAHAMAN BERBASIS BUDAYA TANA LUWU - Guntur, Muhammad; Bungawati, Bungawati; Fitryani, Fitryani (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2024)
There are no textbooks specifically designed to improve students' reading comprehension skills. The aim of the research is to develop a reading comprehension textbook based on Tana Luwu culture using the Content and Language Integrated Learning (CLIL) approach. The type of research used is Research and Development (R&D) with the 4D development model (Define, Design, Development and Disseminate). The research was carried out at the Faculty of Tarbiyah and Teacher Training, involving 25 students. Data collection techniques using observation, interviews and questionnaires. Analyze data qualitatively and quantitatively. Book design is carried out by paying attention to aspects of the material context with reading content starting from the simplest level of reading comprehension to a more complex level by paying attention to identifying learning objectives, selecting material content and planning learning activities. Reading comprehension textbooks have an average validity level of 3.55 with a very valid category so they are suitable for use in the lecture process. After limited trials, based on lecturers' responses, it showed that reading comprehension textbooks had an average practicality level of 3.7 in the very practical category and student responses were 91.7% in the very practical category.